2015
DOI: 10.1021/acs.macromol.5b01162
|View full text |Cite
|
Sign up to set email alerts
|

A Thermoreversible Supramolecular Polyurethane with Excellent Healing Ability at 45 °C

Abstract: We report the synthesis and characterization of a healable, elastomeric shape recovery supramolecular polyurethane whose properties result from self-complementary π−π stacking and hydrogen bonding interactions plus phase separation. ESEM analysis and photographic images have revealed that this material can heal at 45°C in 15 min to recover the mechanical properties of the pristine material with healing efficiencies >99%. This supramolecular polyurethane is also able to recover an applied strain of 25% within 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 76 publications
(117 reference statements)
3
69
1
Order By: Relevance
“…Stronger phase separation between the linker and H‐bonding groups was accomplished through exchange of PIB for a hydrogenated polybutadiene linker, and by including additional aromatic end groups (π–π stacking) . Enhanced network formation was indeed confirmed by X‐ray scattering and resulted in a self‐healing supramolecular material.…”
Section: Adhesives Based On Hydrogen Bondingmentioning
confidence: 95%
“…Stronger phase separation between the linker and H‐bonding groups was accomplished through exchange of PIB for a hydrogenated polybutadiene linker, and by including additional aromatic end groups (π–π stacking) . Enhanced network formation was indeed confirmed by X‐ray scattering and resulted in a self‐healing supramolecular material.…”
Section: Adhesives Based On Hydrogen Bondingmentioning
confidence: 95%
“…To date, the self‐healing polymer systems have been frequently reported by taking advantages of non‐covalent and covalent reversible interaction. The non‐covalent chemistries were employed to construct the self‐healing systems by the pioneers relying on the H‐bonding interaction, ππ stacking, metal–ligand coordination, and electrostatic binding . Those bonds linkages are sensitive and fragile albeit fast.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently some literatures have reported that more than one type of reversible crosslinks can be introduced in polyurethane to form a multifunctional healing system. [19][20][21] Feula et al 22 synthesized a healable, elastomeric supramolecular polyurethane, which could heal at 45 C in 15 min to recover its mechanical properties, resulting from its p-p stacking and hydrogen bonding interaction. In addition, through small-angle X-ray scattering, a micro-separated morphology was observed; it disappeared at 60 C, indicating that supramolecular network was being disrupted.…”
Section: Introductionmentioning
confidence: 99%